Designing of 3D Sensor Chamber for Plasmonic-based Toxic Sensor Detection - Karim, Mohammad Farid Abd; Morsin, Marlia; Nafisah, Suratun; Bakar, Norhayati Abu; Rahman, Munirah Ab (International Journal of Engineering and Technology, 2018)
Plasmonic sensor implementing an optical phenomenon called Localized Surface Plasmon Resonance (LSPR) resulting from the interaction of free electron with electromagnetic field of light at the metal nanoparticles surface. In this study, the plasmonic sensor has been developed for toxic detection in solution form. This system consists of five components which are the light source, duplex fiber optic, sensor chamber, spectrometer and computer. The sensor chamber has been specially designed using SolidWork software and printed using 3D printer with polylactic acid (PLA) material. The sensing activity was done in the sensor chamber with a sliding drawer which is used to place the sensing material or sample. OceanView software was used to analyze the recorded spectrum from the spectrometer. For this project, the experiment of the plasmonic sensor was carried out using targeted analyte namely chlorpyrifos with deionized (DI) water was set as a reference medium. Gold nanoparticles with nanospheres shape used as sensing materials. The sensing parameters are based on changing its intensity and resonance peak position. This plasmonic sensor was compared with UV-VIS spectrometer data to make sure it standardize and function correctly. Besides, the sensing process toward different concentrations of chlorpyrifos from 7.15 mM to 28.60 mM have been done. As a conclusion, the plasmonic sensor was successfully developed for toxic detection in solution form.